Analisis Pengaruh Kepemimpinan, Budaya Organisasi dan Komunikasi Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Karyawan - Edi Sugiono; Gloria Ida Lumban Tobing (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study analyzes the influence of leadership, organizational culture, and Communication on job satisfaction and its impact on employee performance at PT. Usaha Makalingga Mandiri, Jakarta. The research was conducted using survey methods, samples, and questionnaires as the primary data collection tool, and the subjects were 100 respondents. The method of analysis uses the Structural Equation Model (SEM) for hypothesis testing. The results showed that 1) Leadership, Organizational Culture, and Communication directly positively affect Job Satisfaction. 2) Leadership, Organizational Culture, and Communication positively or indirectly affect employee performance through job satisfaction as a mediating variable. 3) Job Satisfaction partially mediates the influence of Leadership, Organizational Culture, and Communication on Employee Performance. 4) Leadership is the variable with the greatest influence on job satisfaction and employee performance. Increased job satisfaction will have an impact in the form of increased employee performance.